Trade openness and income: A tale of two regions - Mariam Camarero; Inmaculada Martínez-Zarzoso; Felicitas Nowak-Lehmenn D.; Cecilio Tamarit (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2013)
In this article we present evidence of the long-run effect of trade openness on income per worker for two regions that have followed different liberalization strategies, namely Asia and Latin America. A model that re-examines these questions is estimated for two panels of Asian and Latin American countries over the 1980-2008 period using a novel empirical approach that accounts for endogeneity as well as for the time series properties of the variables involved. From an econometric point of view, we apply recent panel cointegration techniques based on factor models that account for two additional elements usually neglected in previous empirical literature: cross-dependence and structural breaks. The results point to a positive impact of trade openness in both Asia and Latin America although the size is smaller in the second region. We associate this finding with the degree to which trade was managed in both regions of the developing world.
Keywords: F15; F43; C22; O40; 330; GDP per worker; trade openness; panel cointegration; structural breaks; crosssection dependence; Asia; Latin America